Development of simple equations for effective screening of spurious hemolysis in whole‐blood specimens. (12th July 2014) - Lippi, G.; Pavesi, F.; Avanzini, P.; Chetta, F.; Aloe, R.; Pipitone, S.
Summary Introduction We aimed to identify simple but reliable indices for effective screening of spurious hemolysis in whole‐blood specimens. Methods Thirteen inpatient whole‐blood samples were divided in two aliquots. The former was left untreated, whereas the latter was mechanically hemolyzed by forced aspiration with an insulin syringe. All aliquots were tested on Siemens Advia 2120 and Sysmex XE‐2100. The hemolysis index (HI) was also assessed in centrifuged plasma. Results The mechanical hemolysis generated a 4–40% decrease in red blood cells (RBCs). A statistically significant decrease was observed for hematocrit (Ht) and mean corpuscular volume (MCV), whereas mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and platelet count were increased. The values of hemoglobin (Hb) and white blood cells remained substantially unchanged. Two specific equations ([Ht/Hb] × √MCV and [Ht/Hb] × 100) were developed. Both equations displayed an area under the curve of ≥0.99 for identifying spurious hemolysis, much greater than that of both RBC ghosts and immature platelet fraction. A highly significant correlation was also observed between results of these equations and percentage reduction in RBCs or HI increase. Conclusion Provided that these results will be confirmed in further studies, these equations may provide a reliable means for screening spurious hemolysis in whole‐blood samples.